2020
DOI: 10.1177/1055665620954085
|View full text |Cite
|
Sign up to set email alerts
|

Velar Closing Ratio As a Predictor for the Verlopharyngeal Function After Double Opposing Z-Plasty for Postpalatoplasty Velopharyngeal Insufficiency in Patients With Cleft Palate

Abstract: Background: This study was designed to identify the potential predictors of postoperative velopharyngeal function after double opposing Z-plasty (DOZP) for the treatment of velopharyngeal insufficiency (VPI) in patients who had prior palatoplasty for cleft palate. Methods: This retrospective study reviewed the medical records of consecutive patients who received DOZP for VPI after receiving a prior palatoplasty treating cleft palate between 2004 and 2017. The speech outcome of patient was measured using the Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…17,18 Wu et al recently showed that velar closing ratio is an important predictor of hypernasality resolution in VPD treatment with double-opposing Z-plasties. 19 They noted, however, that the accuracy of velar closing ratio in predicting surgical success is only moderate, a result recapitulated by our analysis: the three patients with abnormal speech scores had relatively low velar closures (<40%) preoperatively, but others within this range had satisfactory results, suggesting that velar closure is not the sole element responsible for postoperative hypernasal speech.…”
Section: Discussionsupporting
confidence: 69%
“…17,18 Wu et al recently showed that velar closing ratio is an important predictor of hypernasality resolution in VPD treatment with double-opposing Z-plasties. 19 They noted, however, that the accuracy of velar closing ratio in predicting surgical success is only moderate, a result recapitulated by our analysis: the three patients with abnormal speech scores had relatively low velar closures (<40%) preoperatively, but others within this range had satisfactory results, suggesting that velar closure is not the sole element responsible for postoperative hypernasal speech.…”
Section: Discussionsupporting
confidence: 69%
“…20 Its effect on the FP outcome in correction of overt cleft palate or secondary VPI has been proven by numerous studies but is inconclusive among the SMCP population. 6,20,29,60,65,66 In this study, preoperative VCR was not indicated as predictive of FP outcome.…”
Section: Discussioncontrasting
confidence: 59%
“…19,27 Besides surgical timing and techniques, various other factors have been proposed as potentially correlated to SMCP outcome, including preoperative velopharyngeal closure ratio (VCR), closure patterns, and severity of anatomic abnormalities and syndromes. 12,[28][29][30] Relevant studies, however, have reported mixed results, and are often confounded by inconsistency of inclusion criteria and relatively small sample size. 28,31 Identification and thorough understanding of prognostic factors is important to the risk-to-benefit evaluation of the SMCP management algorithm.…”
mentioning
confidence: 99%
“…However, better outcomes in younger patients have not been observed in all studies. [36][37][38][39] Nevertheless, VPI results in poor quality-of-life for patients and their parents, 40 and children with severe hypernasality have improved quality-of-life after VPI surgery. 41 Moreover, speech disorders in patients with CP, such as compensatory articulation, may become incorporated into the child's developing phonological rule system and produce a phonological disorder.…”
Section: Discussionmentioning
confidence: 99%